A Pauline approach to the theology of religions - Whitehead, Philip (2017)
The letters of Paul in the New Testament offer a number of insights which are relevant to the Theology of Religions, a branch of Christian Theology concerned with articulating a view of other religions and their adherents. This thesis seeks to offer a constructive approach to Paul’s theology in relation to contemporary Theology of Religions and argue for an exclusivist view, positing that faith in Christ is uniquely the mode of salvation and that there is no basis in Paul’s theology for confidence in other religions as mediatory of salvation or divine revelation. Paul broadly aligns with what is known as the exclusivist view in the Theology of Religions, seeing faith in Christ as necessary for salvation. Paul views both Jew and Gentile non-Christians as standing under divine judgement and oppressed by sin. Gentile religion is viewed as an idolatrous response to natural revelation, and can be demonic in character. It is unable to offer true knowledge of God or to effect salvation. Salvation is achievable only by divine action to rescue, which Paul believes only occurs through faith in Jesus Christ. Paul’s theology divides humanity into two groups using his Adam-Christ dichotomy, with Christians seen as united to Christ and all others being associated with Adam. Conversion is a transfer from the realm of Adam to the realm of Christ, which implies an ontological transformation at the deepest levels of the human person.